1993
DOI: 10.1103/physrevlett.70.1271
|View full text |Cite
|
Sign up to set email alerts
|

Nematic-isotropic phase transition: An extended mean field theory

Abstract: The small magnitude of (T, -T )/T"where T, is the nematic-isotropic phase transition temperature and T denotes the virtual transition temperature, has been a long-standing puzzle in the physics of liquid crystals. We show that by extending the mean field theory to include the isotropic, densitydependent component of the molecular interaction the magnitudes of both (T, -T*)/T, and the density change at the transition automatically become in accord with the experimental values. In addition, the theory yields a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Experimentally observed surface induced mesophase transitions have been studied mainly for the isotropic/nematic transition series [3][4][5]. The nematic/smectic A and isotropic/smectic surface induced transitions have been studied less [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally observed surface induced mesophase transitions have been studied mainly for the isotropic/nematic transition series [3][4][5]. The nematic/smectic A and isotropic/smectic surface induced transitions have been studied less [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnitude of exponent m in crystals, however, saturated thermodynamic properties equation ( 12) has been the subject of continuing discusare not readily available at present. In the literature, sion [ 19,30 ]. Exponent m is often adjusted to ® t experionly pV T data are tabulated for a limited number of mental data for the nematic± isotropic transition [ 30].…”
Section: Pure¯uidsmentioning
confidence: 99%
“…Reasonable values for the parameters in the phenomenological model lead to values of those ratio which are ten times too large as compared with the experimental results. There have been quite a few works [17][18][19][20] to resolve these puzzling aspects. This work substantiated the claim of Tao et al 18 but the value of (Q * − Q NI )/Q NI was found to be inconsistent with the observed values.…”
Section: Introductionmentioning
confidence: 99%
“…There have been quite a few works [17][18][19][20] to resolve these puzzling aspects. This work substantiated the claim of Tao et al 18 but the value of (Q * − Q NI )/Q NI was found to be inconsistent with the observed values. In the present work we have showed how the higher order term in the Landau-de Gennes free energy expansion gives the consistent results of (T NI − T * )/T * and (Q * − Q NI )/Q NI .…”
Section: Introductionmentioning
confidence: 99%